RESPON PERTUMBUHAN DAN HASIL TANAMAN MELON (Cucumis melo, L.) AKIBAT PEMBERIAN TEPUNG CANGKANG TELUR DENGAN BERBAGAI JENIS PUPUK KANDANG - Sevin drajuta (Jurnal Pertanian UMSB: Penelitian dan Kajian Ilmiah Bidang Pertanian, 2017)
Research "Growth Response and Result of Melon Plant (Cucumis melo, L.) due tothe provision of Egg Shell Flour with various Kinds of Manure". has been conducted in theExperimental Garden of Agriculture Faculty of Muhammadiyah University of WestSumatera, from February to May 2017. The purpose of this research is to get the bestmanure with eggshell flour combinations for the growth and yield of melon plants.This study used a Completely Randomized Design (RAL), the observations wereaveraged and analyzed by F test at 5% real level, with 4 treatments and 4 replications sothat the total number of plots was 16 plots. Plot size 1.2 m x 2m, polybag distance 60 cm x50 cm, so that each plot there are 8 polybags with 3 plants as sample. The treatments arevarious types of manure with additional eggshell flour as follows; A. Without fertilizer,B.chicken manure, C. Cow manure and D. Goat Manure. Observations in this studyinclude: when the field appeared, the height of the plant, the number of branches, thenumber of leaves, when the flower appeared, the diameter and length of the fruit, and theweight of the melon fruitThe results showed that the effect of chicken egg shell powder in various types ofmanure is chicken manure, cow manure and goat manure on the growth and production ofmelon Cucumis melo L. var. Amanta F1 has not had any significant effect on the growthand production of melon plants. Provision of chicken manure provides the highest growthand production potential of melon plants and is better than cow manure and goat manure